Medical social work practice in India emerging trends and perspectives - Tanu Girotra (New Delhi Sultan Chand & Sons, 2019)
The purpose of this book is to serve social work, health care professionals, practitioners and educators to develop the conceptual clarity of emerging trends, approaches, challenges and perspectives in Medical Social Work field and to explore a wide range of social work services in Medical set up. This book offers the most comprehensive and insightful analysis of Social Work Practice in a Hospital Setting and covers the diverse field of Medical Social Work. This book provides social work students, educators and practitioners with the relevant knowledge, skills, ethical considerations and how to implement this knowledge in the emerging field of Medical social work. This comprehensive book thoroughly integrates Medical social work theory and practice and provides an excellent opportunity for understanding particular competencies and interventions. It covers the wide array of roles performed by Medical Social Workers in a Hospital Settings, Ethical issues and inclusion of Health schemes and programmes in India
Keywords: Social Work